2020
DOI: 10.1002/cplu.202000125
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Physicochemical and Antimicrobial Properties of Liposomes Loaded with (+)‐Usnic Acid

Abstract: +)-Usnic acid (UA) is a natural substance that displays pharmacological activity, but it is barely soluble in water, so it was included in liposomes in order to study its properties. First, the effects of phospholipid structure and loading methodology on UA entrapment efficacy were evaluated. Then, the physicochemical and biological properties (UA delivery efficacy to Staphylococcus aureus bacterial cells) of different liposome formulations containing structurally related amphiphiles derived from L-prolinol we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In fact, differences in the lipid chain length and/or in the degree of unsaturation affected the features of the aggregates they form [36,37]. Moreover, in a previous work, we observed that subtle variations of the polar headgroup and/or of the alkyl chain region of minor components of liposome formulations influenced the antibacterial activity of the active principle included in the vesicle bilayer [38]. Scheme 2.…”
Section: Introductionmentioning
confidence: 89%
“…In fact, differences in the lipid chain length and/or in the degree of unsaturation affected the features of the aggregates they form [36,37]. Moreover, in a previous work, we observed that subtle variations of the polar headgroup and/or of the alkyl chain region of minor components of liposome formulations influenced the antibacterial activity of the active principle included in the vesicle bilayer [38]. Scheme 2.…”
Section: Introductionmentioning
confidence: 89%
“…35 Briefly, for the antibacterial susceptibility, 100 μL of a bacterial suspension in a 0.9% saline solution (NaCl) at a concentration of 5 × 10 –5 CFU/mL was added to the wells of a 96-well microtiter plate containing 100 μL of 2-fold serially diluted free UA and quatsomes loaded with UA (with both loading methodologies) in cation-adjusted Mueller–Hinton broth. The experiments were then carried out as reported in ref ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous investigation, liposomes containing analogous structurally related l -prolinol derivatives showed a good ability to efficiently deliver UA to S. aureus bacterial cells. 10 Because the biological activity of UA in some cases can be related to the antioxidant one, 26 we assessed also the antioxidant effectiveness of quatsomes/UA. In fact, we previously showed that this property can significantly vary as a function of the composition of the systems in which it is included.…”
Section: Introductionmentioning
confidence: 99%
“…They are zwitterionic amphiphilic compounds at physiological pH, bearing a strong polar N–O bond with a high electron density on the oxygen atom [ 37 ]. In particular, these surfactants, coming from selective modification of their amphiphilic molecular structure, have opened the scenario to a plethora of systems [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], providing different superstructures by their self-assembly and co-assembly with other materials. They show multifunctional capabilities and are used in several industrial applications, such as washing-up products and laundry detergents, foaming and wetting agents, softeners and thickeners, besides being components of hair and body care products [ 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%